5(6z-1)-2(z+3)=21(z+1)

Simple and best practice solution for 5(6z-1)-2(z+3)=21(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6z-1)-2(z+3)=21(z+1) equation:


Simplifying
5(6z + -1) + -2(z + 3) = 21(z + 1)

Reorder the terms:
5(-1 + 6z) + -2(z + 3) = 21(z + 1)
(-1 * 5 + 6z * 5) + -2(z + 3) = 21(z + 1)
(-5 + 30z) + -2(z + 3) = 21(z + 1)

Reorder the terms:
-5 + 30z + -2(3 + z) = 21(z + 1)
-5 + 30z + (3 * -2 + z * -2) = 21(z + 1)
-5 + 30z + (-6 + -2z) = 21(z + 1)

Reorder the terms:
-5 + -6 + 30z + -2z = 21(z + 1)

Combine like terms: -5 + -6 = -11
-11 + 30z + -2z = 21(z + 1)

Combine like terms: 30z + -2z = 28z
-11 + 28z = 21(z + 1)

Reorder the terms:
-11 + 28z = 21(1 + z)
-11 + 28z = (1 * 21 + z * 21)
-11 + 28z = (21 + 21z)

Solving
-11 + 28z = 21 + 21z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-21z' to each side of the equation.
-11 + 28z + -21z = 21 + 21z + -21z

Combine like terms: 28z + -21z = 7z
-11 + 7z = 21 + 21z + -21z

Combine like terms: 21z + -21z = 0
-11 + 7z = 21 + 0
-11 + 7z = 21

Add '11' to each side of the equation.
-11 + 11 + 7z = 21 + 11

Combine like terms: -11 + 11 = 0
0 + 7z = 21 + 11
7z = 21 + 11

Combine like terms: 21 + 11 = 32
7z = 32

Divide each side by '7'.
z = 4.571428571

Simplifying
z = 4.571428571

See similar equations:

| y^4+y^2-42=0 | | -13x+8x= | | -3(t-4)-(t+9)=3 | | 1.5-2.5x+8.5=-2.5 | | 15n-3/2=6 | | 44=122 | | 7-2-(-8)-11= | | -8(t-3)-(t+1)=8 | | -14+58-(-13)-16= | | 5w^2=5w-10 | | 5+8(x-1)=5-2(x-9) | | 36+(-52)+31= | | -15+12+(-27)+25= | | y=9(0)+3 | | 5+5(x-6)=6-6(x-3) | | y=9(3)+3 | | 2+4=-6 | | y=93+3 | | h=-4t^2+20t+7 | | 16x^2+50x+3.5=0 | | 3x^2-34x=-4x^2-7x-18 | | ln(9x+4)-lnx=ln(10) | | log(6x-5)+log(x+5)=1 | | 96=17x-5x | | 2x^2+5x+9=0 | | 9u+8/5+5u+5/4=12 | | 10x^2+25x+45=0 | | 3x+2x+4x=15+8 | | -5(a-2b+3a-2b)=2(-2-3b) | | 0=9x+3 | | 3y^2-10y+7=0 | | 9q+15q= |

Equations solver categories